2009
DOI: 10.1128/mcb.01352-08
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissection of Human and Mouse POT1 Proteins

Abstract: The single-stranded telomeric DNA binding protein POT1 protects mammalian chromosome ends from the ATR-dependent DNA damage response, regulates telomerase-mediated telomere extension, and limits 5-end resection at telomere termini. Whereas most mammals have a single POT1 gene, mice have two POT1 proteins that are functionally distinct. POT1a represses the DNA damage response, and POT1b controls 5-end resection. In contrast, as we report here, POT1a and POT1b do not differ in their ability to repress telomere r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
146
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 29 publications
2
146
0
Order By: Relevance
“…Using a filter-binding assay, we determined the K D of hPOT1-D12 to be 6.3 AE 3.5 nM and that for mPOT1A-D12 to be 0.9 AE 0.3 nM, values that agree well with previous reports (10,28). To quantify the defect in binding for a particular dodecamer, we calculated the ratio of the K D for the complex formed by that dodecamer to the K D for the analogous complex formed by D12 (designated as "fold increase of K D " in Table 1).…”
Section: Quantitation Of the Deleterious Effects Of Ribonucleotide Susupporting
confidence: 89%
See 1 more Smart Citation
“…Using a filter-binding assay, we determined the K D of hPOT1-D12 to be 6.3 AE 3.5 nM and that for mPOT1A-D12 to be 0.9 AE 0.3 nM, values that agree well with previous reports (10,28). To quantify the defect in binding for a particular dodecamer, we calculated the ratio of the K D for the complex formed by that dodecamer to the K D for the analogous complex formed by D12 (designated as "fold increase of K D " in Table 1).…”
Section: Quantitation Of the Deleterious Effects Of Ribonucleotide Susupporting
confidence: 89%
“…We observed that mouse POT1A, the essential POT1 paralog in mice (7), serves as an excellent source of recombinant mammalian POT1, because it can be obtained readily from overexpression in bacteria (unlike hPOT1, which is isolated after expression in baculovirus-infected insect cells). To examine the effects of ribonucleotide substitution within the telomeric sequence on mammalian POT1 binding, we carried out a parallel binding analysis of hPOT1 and mPOT1A with oligonucleotides that contain two telomeric repeats terminating in TAG-3 0 , which is optimal for mPOT1A and hPOT1 binding (27,28).Like hPOT1 (6), mPOT1A failed to bind an all-RNA telomeric dodecamer R12 under conditions in which it formed a stable complex with D12 ( Fig. 1A; oligonucleotide sequences in Table 1).…”
mentioning
confidence: 99%
“…Critically shortened telomeres are recognized as DSBs and are highly susceptible to be repaired by HR or NHEJ pathways (Palm et al, 2009, Rai et al, 2010. However, unequal exchange of telomeric sequences by HR or misrepair by C-and/or ALT-NHEJ, can lead to loss of cell viability or can result in genomic instability and cancer.…”
Section: Alt-nhej At Dysfunctional Telomeresmentioning
confidence: 99%
“…3 Among these shelterin components, TRF1 and TRF2 interact with telomeric dsDNA in a sequence-specific manner, whereas POT1, in a complex with TPP1, binds to protection, 20,41,42 they are neither necessary nor sufficient for the localization of POT1 to telomeres. 8,20,43 Indeed, while a point mutation in the OB fold abolished POT1a binding to telomeric ssDNA in vitro, this mutant efficiently localized to telomeres in vivo.…”
mentioning
confidence: 99%
“…In both human and mouse, the abilities of POT1 and POT1a/b to bind TPP1 are critical for their functions in telomere protection. 8,13,[42][43][44] A POT1 mutant lacking the TPP1-binding domain failed to localize to telomeres. 8 Furthermore, a POT1 mutant unable to bind TPP1 failed to prevent RPA accumulation at telomeres, 20 suggesting that the role of POT1 in antagonizing RPA binding is dependent upon its interaction with TPP1.…”
mentioning
confidence: 99%